New prenylated bibenzyls from Bornean liverwort Acrobolbus saccatus - Ng, Shean Yeaw; Takashi Kamada; Phan, Chin Soon; Monica Suleiman; Charles Santhanaraju Vairappan (2018)
Liverworts are the most primitive terrestrial plant which known to produce unique and wide variety of compounds. Ethyl acetate crude extract was subjected to several chromatographic techniques for purification. Three new compounds, saccatenes A-C (1-3) were isolated together with two known prenyl bibenzyl derivative, 2,2-dimethyl-5-hydroxy-6-carboxy-7-(2-phenylethyl) chromene (4) and radulanin A-5-one (5) from the Bornean liverwort Acrobolbus saccatus (Hook.) Trevis collected from Mountain Trus Madi, Sabah, Malaysia. The structures of the three new metabolites were established by analyses of the spectroscopic data (1D NMR, 2D NMR, HRESIMS and IR), and the antibacterial activity against eight selected human pathogenic species of bacteria were tested.